Light management in plastic–paper hybrid substrate towards high-performance optoelectronics. Issue 7 (6th June 2016) - Yao, Yonggang; Tao, Jinsong; Zou, Jianhua; Zhang, Bilun; Li, Tian; Dai, Jiaqi; Zhu, Mingwei; Wang, Sha; Fu, Kun Kelvin; Henderson, Doug; Hitz, Emily; Peng, Junbiao; et al.
Abstract : We integrated plastic into mesoporous paper to achieve a new type of substrate plastic–paper for high performance optoelectronics. Abstract : Optoelectronic devices are ubiquitously built on substrates. To increase the efficiencies of light coupling into and out of optoelectronic devices, such as thin film solar cells and flexible lighting, a substrate with high transmittance and high haze is desired. Unfortunately, optical transmittance and optical haze are usually contrasting to each other in common substrates: plastic is highly transparent but with a low optical haze, whereas paper has a high optical haze but a low total transmittance. Herein, we combine these two materials through a simple templated infiltration approach to achieve a new type of substrate, plastic–paper, which has a high optical transmittance (>85%) and high transmittance haze (>90%) in a broadband wavelength. The plastic–paper has an ultra-flat surface, is mechanically flexible, durable in different solvents and compatible with standard processing in semiconductors, which are shown by organic light emitting diodes (OLED) fabricated directly onto the plastic–paper substrate. Plastic–paper leads to improved light coupling into and out of optoelectronic devices and demonstrates an improvement in efficiency for both OLED and typical GaAs solar cells. The fabrication method is also fully scalable with roll-to-roll production. The newly developed low-cost, high-performance transparent and hazy substrate is attractive for a range of optoelectronic devices.